EVOLUÇÃO DA EDUCAÇÃO SUPERIOR A DISTÂNCIA NO BRASIL: UMA ANÁLISE A PARTIR DE PROCESSOS DE INSTITUCIONALIZAÇÃO - Jorge da Silva Correia-Neto (Universidade Federal de Santa Catarina, 2017)
Distance education in Brazil gains prominence from the 2000s, with the Open University ofBrazil and with its insertion on the National Educational Plan 2001-2010, that intendedtoprovide the superior education to 30% of the Brazilian population from 18 to 24 years old.Aiming to reflect over this reality, the study discussed the evolution of distance education inBrazil, using the institutional theory lenses, questioning how this process ofinstitutionalization has been going on through the last decades. To answer this questioning,this manuscript was developed in two steps: the first one presents the history of distanceeducation in Brazil and the second one shows its main signsof institutionalization. Themethodological procedures involved the content analysis of two deep interviews and anextensive document analysis. As results, this manuscript points out that the process ofinstitutionalization of distance education in Brazilis dynamic and permanent, and thatinstitutional theory lenses are relevant to describe transformations that occurs in strategicareas such as distance education. The study also presents future work.